2017
DOI: 10.1093/cid/cix535
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aerosols Generated During Patient Care Activities

Abstract: In this study, significant aerosol generation was only observed during NMA, both alone and during bronchoscopy. Minimal viable bacteria were recovered, mostly common environmental organisms. Although more research is needed, these data suggest that some of the procedures considered to be aerosol-generating may pose little infection risk to HCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 32 publications
4
84
0
3
Order By: Relevance
“…The finding that bronchoscopy was not associated with elevated mean ultrafine and respirable aerosol concentrations ( Table 2), is consistent with O'Neil et al, [3] who used these same instruments (and others), and observed aerosol number and mass concentrations to be elevated only during bronchoscopies with nebulized medication administration. However, Lavoie et al, [4] who used a Ultraviolet Aerodynamic Particle Sizer (UV-APS) to measure particles 0.5-15 mm diameter, found that the number concentrations of fluorescent particles (containing biological materials) and non-fluorescent particles were 3-times and 124-times greater during bronchoscopy procedures than at the beginning or end of the day (occupancy at these times was not described), respectively.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The finding that bronchoscopy was not associated with elevated mean ultrafine and respirable aerosol concentrations ( Table 2), is consistent with O'Neil et al, [3] who used these same instruments (and others), and observed aerosol number and mass concentrations to be elevated only during bronchoscopies with nebulized medication administration. However, Lavoie et al, [4] who used a Ultraviolet Aerodynamic Particle Sizer (UV-APS) to measure particles 0.5-15 mm diameter, found that the number concentrations of fluorescent particles (containing biological materials) and non-fluorescent particles were 3-times and 124-times greater during bronchoscopy procedures than at the beginning or end of the day (occupancy at these times was not described), respectively.…”
Section: Discussionsupporting
confidence: 86%
“…With respect to the former limitation, interpretation of these data for infection risk among healthcare workers requires an assumption about the concentration of pathogens in respiratory secretions and aerosols. The UV-APS instruments, such as have been used by others, [3,4] are able to identify bioaerosols, but are not able to distinguish between pathogens, commensal microorganisms, and other particles of biological origin, such as human epithelial cells including human skin cells. Future work should capitalize on epidemics and pandemics, such as Thompson et al, [5] to characterize pathogen emission, transport, and fate during bronchoscopy procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations